1975
DOI: 10.1159/000175660
|View full text |Cite
|
Sign up to set email alerts
|

Some Metabolic Effects of Prolonged Feeding of Starch, Sucrose, Fructose and Carbohydrate-Free Diet in the Rat

Abstract: Male rats of the ASL Wistar strain were fed from weaning on starch, fructose or carbohydrate-free diets for 4 and 12 weeks. In addition, further groups were fed for 24 weeks on starch, sucrose or carbohydrate-free diets. Livers were examined for gross composition, glucose-6-phosphatase activity and in vitro lipogenesis and glucose oxidation. Intestinal sucrase was also measured. Dietary fructose and the carbohydrate-free diet induced an enlargement of the livers after 12 weeks feeding, when expressed per 100 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The increase in liver weight by fructose feeding was documented by Tuovinen and Bender 46 . Similarly, Huang et al 47 reported that fructose promotes obesity more than glucose as fructose enhances food intake and does not stimulate thermogenesis.…”
Section: Discussionmentioning
confidence: 78%
“…The increase in liver weight by fructose feeding was documented by Tuovinen and Bender 46 . Similarly, Huang et al 47 reported that fructose promotes obesity more than glucose as fructose enhances food intake and does not stimulate thermogenesis.…”
Section: Discussionmentioning
confidence: 78%
“…Using the hyperinsulinemic euglycemic clamp, fructose-fed rats were shown to have an impaired ability to suppress hepatic glucose production and to eliminate peripheral glucose (22). An increase in the gluconeogenic enzymes glucose-6-phosphatase and phosphoenolpyruvate carboxykinase has been reported for the liver of fructose-fed rats (22)(23)(24)(25)(26)(27). Furthermore, a high-fructose diet was reported to reduce hepatic glycogen synthesis (24,27).…”
Section: Discussionmentioning
confidence: 99%
“…Fructose or sucrose feeding has been shown to modify multiple aspects of carbohydrate metabolism, causing a decrease in glucose oxidation in hepatic tissue, 21 adipose tissue, 22 and striated muscle tissue. 23 Also, hepatic gluconeogenesis is enhanced, 2446 and hepatic glycogen synthesis is impaired.…”
Section: Fructose Feeding Fuel Metabolism and Insulin Actionmentioning
confidence: 99%